Gendered Access to Livelihood Assets among Refugees in Kakuma Refugee Camp, Turkana County, Kenya - Kinyanjui, Mary Nyambura; Obebo, Forah (International Journal of Economics, 2025)
Purpose: The management of refugees in Kenya is guided by a comprehensive policy framework, with efforts from global, national, regional, and humanitarian actors aimed at fostering self-reliance and economic inclusion for refugees. Despite this, female refugees continue to face challenges related to limited access to resources and heightened vulnerability. This paper analyses the gendered access to livelihood assets among refugees in Kakuma refugee camp, Turkana County. The study utilises cross-sectional data from the United Nations High Commissioner for Refugees database collected in 2019, which included 2,217 randomly sampled households. Methodology: The study employs the Human Capital Theory, Sustainable Livelihood Approach, and a multidimensional vulnerability index to examine vulnerability from a gendered perspective and how gender dynamics influence refugees’ access to assets. Following Heteroscedasticity, Model Specification, and Goodness of Fit tests, the study implemented a Fractional Regression and Multivariate Logistic Model to empirically analyse the data. Findings: The findings indicate that gender significantly influences vulnerability in many refugee households, with women being more susceptible. Furthermore, women refugees are 0.104 per cent less likely to engage in farming and 4.15 per cent less likely to possess a bank account. In addition, women-headed households are more food insecure with a higher probability of limiting meal portions, relying on less preferred food and borrowing money to buy food. Unique Contribution to Theory, Practice and Policy: The study findings reveal that male-headed households also experience vulnerability and lack access to essential resources. This study recommends policies that target both men and women, recognising that male refugees are equally vulnerable.